Treasures from the Oxus the art and civilization of Central Asia - Vidale, Missimo; Ricciardi, Valerio (London : I.B. Tauris, 2017)
The great river civilization of the Oxus is one of the forgotten jewels of the ancient world.
Map on lining papers.
Keywords: Asia, Central -- Antiquities; Amu Darya -- Antiquities; Asia, Central -- History